1998
DOI: 10.1001/archderm.134.3.319
|View full text |Cite
|
Sign up to set email alerts
|

Acute Urticaria in Infancy and Early Childhood

Abstract: To establish the clinical, etiological, and prognostic features of acute urticaria in infancy and early childhood and to define its optimal management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
89
2
20

Year Published

2001
2001
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 166 publications
(114 citation statements)
references
References 18 publications
3
89
2
20
Order By: Relevance
“…Harris et al [4] found a recovery rate of 58% in 94 children with CU after a 1-year follow-up. Mortureux et al [19] reported a recovery rate of 94.7% in 57 children, most of whom had acute urticaria. Kauppinen et al [18] reported a 47% recovery rate with a mean follow-up of 3.8 years, with physical urticaria having the worst prognosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Harris et al [4] found a recovery rate of 58% in 94 children with CU after a 1-year follow-up. Mortureux et al [19] reported a recovery rate of 94.7% in 57 children, most of whom had acute urticaria. Kauppinen et al [18] reported a 47% recovery rate with a mean follow-up of 3.8 years, with physical urticaria having the worst prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…CU can cause significant morbidity in the form of school absences, low school performance, and poor quality of life, and patients rely heavily upon healthcare services compared to patients with other allergic diseases [14]. However, information about the natural course of the disease is drawn mainly from adult studies [15,16,17], and there is little information available regarding children [4,18,19]. …”
Section: Introductionmentioning
confidence: 99%
“…Known etiologies of chronic urticaria in children vary from 21% to 83% (3)(4)(5)(6). Infectious causes of chronic urticaria are more common in children than adults (5,7). The association between Helicobacter pylori (H. pylori) and urticaria can be considered as another cause of disease (8)(9)(10).…”
Section: Contextmentioning
confidence: 99%
“…Yiyecek alerjileri de (özellikle inek sütü) erişkinlere göre çok daha yaygın bir sebeptir. 3,4 Akut ürtikerde atakların kısa sürmesi ve kendini sınırlayan tek bir atak olması nedeniyle bazı otörler etyolojiyi araştırmak için geniş tetkikler yapılmasını önermemektedir. 5 Bu çalışmada akut ürtiker hastalarının ayrıntılı klinik ve demografik özellikleri incelenmektedir.…”
Section: Gi Riflunclassified